Strategic Management in the Context of Public Policy of Education at the North Aceh Regency Education and Culture Office - Jamaluddin; Mesiono; Abdurahman (Yayasan Darussalam Bengkulu, 2026)
Minimum Service Standards (SPM) are intended to guarantee equitable basic education services; however, their implementation in decentralized regions often remains uneven. This study examined how strategic management shaped the acceleration of education SPM achievement at the North Aceh Regency Education and Culture Office. A qualitative case-study design was employed. Data were collected in 2026 through semi-structured interviews with five purposively selected informant groups: service leadership, facilities and infrastructure managers, planning and cross-sector actors, school supervisors, and school principals. Non-participant observations and document reviews of planning, budgeting, performance, SPM, Dapodik/EMIS, and coordination records complemented the interviews. Data were analyzed using the Miles, Huberman, and Saldaña interactive model and validated through source and technique triangulation, member checking, and audit trails. The findings showed that SPM had been incorporated into formal planning and reporting but had not been fully operationalized as an outcome-based performance target. The overall case-based analytic reach score was 61.30%, while planning, budgeting, and data utilization showed the lowest achievement at 56.00%. Infrastructure management remained reactive, teacher and facility provision was uneven, and cross-sector coordination was not yet institutionalized. Geographical remoteness also continued to constrain access, supervision, and service equity. These findings indicate that regulatory commitment alone cannot ensure SPM achievement without integrated leadership, spatially responsive planning, targeted budgeting, systematic data use, and formal interagency coordination. The study is limited to one institutional case and purposively selected informants; therefore, its findings are not statistically generalizable. Future studies should compare districts and apply longitudinal monitoring to assess the sustainability of strategic interventions.